Microsatellite DNA Loci for Population Studies in Brazilian Chicken Ecotypes - Clementino, C.S.; Barbosa, F.J.V.; Carvalho, A.M.F.; Costa-Filho, R.A.R.; Silva, G.R.; Campelo, E.G.; Britto, F.B.; Diniz , F.M. (International Journal of Poultry Science, 2010)
In poultry, the reduction in genetic variability of native chicken populations has led to the use of microsatellites in many genetic studies of chicken ecotypes. To be of maximum usefulness as a genetic marker, microsatellite primers should be amplifying the same locus other than the source of the primer sequence in different populations. Even in closely related lines or breeds microsatellite genotyping errors may be introduced from primer mismatches as a result of mutations in the primer binding sites. Therefore, the selection, use and optimization of microsatellites are considered to be a fundamental step towards full success in genetic studies. Herein, 20 microsatellite loci are presented with great potential for diversity studies in Brazilian chicken ecotypes. The analyses of these ecotypes revealed a total of 191 robust alleles, ranging from three to 18, with an average of 9.6 alleles per locus. The average observed heterozygosity was 0.785, while the mean expected heterozygosity was 0.688. Additionally, the mean polymorphic information content value (0.731) further reflected high level of polymorphism across all microsatellite loci. The topology of the dendrogram constructed with the neighbour-joining method showed probable patterns of relationship and genetic differentiation among the individual ecotypes. Overall, microsatellite loci have proven to be highly useful for studying the variability of chicken ecotypes in the Mid-North region of Brazil.